Stroke in Saskatchewan : a regional sample - Bharadwaj, Lalita (2013)
The latest evidence indicates that 50,000 Canadians will experience a stroke in 2013. The hospital care, rehabilitation, and long term care associated with a stroke places a significant burden on our health care system. Lost productivity and premature death have an immeasurable impact on communities in our province as well as the rest of the country. Small, less populated regions such as Saskatchewan may be underrepresented in national data utilized in the development of national prevention and treatment strategies across the country. The absence of local research has necessitated the use of national information to guide prevention, treatment education and programming in Saskatchewan. The goals of this study was to provide a descriptive profile of stroke and transient ischemic attack cases admitted to Royal University Hospital over the period of April 1, 2009 to March 31st, 2010 and to assess the acute management of these cases as defined in the Canadian Best Practice Recommendations for Stroke Care (Strategy, 2010). A randomized sample of 200 cases 55 years and older was selected for a retrospective descriptive study involving review of adult stroke case records. Personal demographics and healthcare performance through the use of measures provided in The Canadian Best Practice Recommendations for Stroke Care (Canadian Stroke Network (CSN) and Heart and Stroke Foundation of Canada (HSFC), 2010) were evaluated. The results indicated many similarities to available national information on type of stroke, risk factors, gender, and age. Hospital adherence to national guidelines comparing selected indicators was exceeded in some areas, and met in most. The remaining indicators provide an opportunity for improvement and possibly more research. This regional information supplements the available Canadian information and could be used to guide planning and care strategically targeting Saskatchewan residents and increasing their potential for success.